Factors Affecting Nodal Status in Breast Cancer - Diaa Aboelata; Amr Sarhan; Mohammed Abo Mira; Sami Mohammed (International Journal of Medical Arts, 2020)
Background: Nodal status in breast cancer [BC] is the most prognostic factor for survival and prognosis, and affects treatment decisions. Nodal status had reciprocal relation with pre- and post-operative factors. All these reflect the crucial importance of nodal status in BC. Aim of the work: Evaluation of pre- and post-operative factors related to nodal status in breast cancer. Patients and Methods: The current work included 40 patients with confirmed BC, who had been scheduled for modified radical mastectomy or conservative breast surgery with axillary evacuation. All were assessed in a systematic manner preoperatively. In addition, an intraoperative and post-operative evaluation had been carried out. Postoperative histopathological examination of excised tissues had been done for all specimens. Both intra- and post-surgical complications and factors associated with positive nodal status were documented.  Results: The most significant factors associated with high positive nodal status were age (patient ≤ 45 years was significantly associated with increased positive nodes when compared to > 45 years (37.68±35.23 vs 17.66±19.45 respectively), obesity (30.66±27.33 vs 18.49±25.07 nodes for obese and lean individuals respectively)., tumors greater than 2 cm, positivity of the human-epidermal-growth-factor receptor 2 [Her2]/neu, positive lymphovasular invasion, tumors of the upper quadrant, and the type of histopathology. Conclusion: Nodal status affected by pre- and post-surgery factors (e.g., age, obesity, tumor site, tumor size, Her2/neu, lymphovascular invasion and histopathological type of the tumor). Thus, these factors help in planning of the treatment such as the type of surgery, endocrine therapy, radiation therapy and the adjuvant chemotherapy.